The Role of Index, Icon, and Symbol in the Official Rebrand Introduction Video for Burger King - Risnawati, Ela; Sakinah, R. Myrna Nur (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Advertising plays a vital role in brand communication by employing various semiotic elements to convey messages effectively. However, the use of Charles S. Peirce's semiotic framework in analyzing rebranding strategies remains underexplored. This study examines the application of semiotic elements index, icon, and symbol in Burger King’s official rebrand introduction video to highlight its message of modernization and innovation. Using qualitative methods, the research identifies 10 distinct signs within the video: 3 icons, 1 index, and 6 symbols. The visual transformation of the brand identity, serving as an index, signifies Burger King's commitment to innovation and customer focus. Icons, such as mouthwatering depictions of burgers and fries, represent the brand’s core products, while symbols, including the new logo and textual elements, convey cultural meanings tied to the brand’s identity. Findings reveal that these signs effectively combine to project Burger King as a modern, innovative, and customer-oriented brand, addressing competitive market demands. This semiotic analysis underscores the importance of blending visual and symbolic elements in branding to shape consumer perceptions and reinforce brand identity. Future research should explore similar strategies in other industries to expand understanding of semiotic applications in advertising.